Assessment of Antidiabetic and Cyto-Regenerative Activity of Ficus carica through Gene Expression Analysis in Diabetic Rat Model - Saleem, Makkia; Sharif, Mian Kamran; Butt, Masood Sadiq; Faisal, Muhammad Naeem (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Diabetes mellitus is a metabolic disease of the endocrine system, characterized by chronic hyperglycemia resulting from insulin resistance or defective insulin production. Among the complementary and alternative medicines, diet-based approaches are gaining popularity worldwide for the management of it. Ficus carica, one of the oldest plants cultivated on the earth, is rich in phytochemicals including anthocyanins, phenolics, flavonoids, and organic acids. The present study was designed to analyze the therapeutic potential of dried fig and extract for their potential against hyperglycemia and related complication in the diabetic rat model. Diabetes was induced by using alloxan monohydrate and divided into five groups including Negative-, Positive-, standard drug- group, treated-I (given extract), and treated-II (given 10% dried figs). Fig extract was administered through the intragastric tube, and fig paste was mixed in the feed of the experimental group, and then rats were decapitated after 6 weeks to collect the blood and serum. At the end of the study, biochemical analysis such as fasting blood glucose (FBG), serum glucose, and insulin was performed. Histopathological study of the pancreas showed cell deformation in the positive control group whereas damage was reversed in treated groups. The pancreas was also saved for gene expression analysis. The results revealed that the positive control group has lower expression of INS-1, INS-2, Pdx-1, amylin, and GLUT-2 genes. Results revealed that serum glucose and FBG started to normalize after the administration of treatment (Glibenclamide, dry fig, and fig fruit extract), and insulin concentration also started to improve. 10% dried fig was more effective to control hyperglycemic conditions, which might be due to the presence of fiber. However, the gene expression was more modulated in the group treated with fig extract. The findings of current research suggested the utilization of fig and fig-based products because of their potential to reverse the damage induced by the alloxan or stressors of daily life.